Goal setting in the principal-agent model: Weak incentives for strong performance - Brice Corgnet; Joaquín Gómez-Mi\~nambres; Roberto Hernán-González (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
We study a principal-agent framework in which principals can assign wage-irrelevant goals to agents. We find evidence that, when given the possibility to set wage-irrelevant goals, principals select incentive contracts for which pay is less responsive to agents' performance. Agents' performance is higher in the presence of goal setting despite weaker incentives. We develop a principal-agent model with reference-dependent utility that illustrates how labor contracts combining weak monetary incentives and wage-irrelevant goals can be optimal. The pervasive use of non-monetary incentives in the workplace may help account for previous empirical findings suggesting that firms rely on unexpectedly weak monetary incentives.
Keywords: C92; D23; M54; 330; principal-agent models; incentive theory; non-monetary incentives; goal setting; reference-dependent utility; laboratory experiments